2019
DOI: 10.1021/jacs.8b13402
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design via Synergistic Combination Leads to an Outstanding Deep-Ultraviolet Birefringent Li2Na2B2O5 Material with an Unvalued B2O5 Functional Gene

Abstract: Birefringent materials, the key components in modulating the polarization of light, are of great importance in optical communication and the laser industry. Limited by their transparency range, few birefringent materials can be practically used in the deep ultraviolet (DUV, λ < 200 nm) region. Different from the traditional BO3- or B3O6-based DUV birefringent crystals, we propose a new functional gene, the B2O5 unit, for designing birefringent materials. Excitingly, the synergistic combination of Li4B2O5 and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
142
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 216 publications
(146 citation statements)
references
References 64 publications
3
142
1
Order By: Relevance
“…0.105 at 1064 nm) and Rb 3 VO(O 2 ) 2 CO 3 (calc. 0.075 at 1064 nm), as well as the recently reported Li 2 Na 2 B 2 O 5 (0.095 at 532 nm), Ca(BO 2 ) 2 (0.1355 at 546 nm), Sn 2 B 5 O 9 Cl (0.168 at 546 nm), NaCa 4 V 5 O 17 (calc. 0.1 at 1064 nm), and LiHgPO 4 (calc.…”
Section: Figuresupporting
confidence: 83%
See 1 more Smart Citation
“…0.105 at 1064 nm) and Rb 3 VO(O 2 ) 2 CO 3 (calc. 0.075 at 1064 nm), as well as the recently reported Li 2 Na 2 B 2 O 5 (0.095 at 532 nm), Ca(BO 2 ) 2 (0.1355 at 546 nm), Sn 2 B 5 O 9 Cl (0.168 at 546 nm), NaCa 4 V 5 O 17 (calc. 0.1 at 1064 nm), and LiHgPO 4 (calc.…”
Section: Figuresupporting
confidence: 83%
“…Large anisotropic polarizability in crystals will give rise to large birefringence. Some strategies have been developed to enhance the birefringence of a crystal: 1) Introducing second‐order Jahn–Teller distorted polyhedra with d 0 cation (V 5+ , Mo 6+ ) centers; related compounds include YVO 4 (Δ n =0.225 at 633 nm) and NaCa 4 V 5 O 17 (Δ n =0.1 at 1064 nm); 2) introduction or condensation of delocalized π‐conjugated planar groups such as BO 3 groups; for example, Pan and co‐authors recently reported two borates, Li 2 Na 2 B 2 O 5 and CaB 2 O 4 , which are composed of condensed B 2 O 5 dimers and [B 2 O 4 ] ∞ infinite chains and exhibit large birefringences of Δ n =0.095 at 532 nm and Δ n =0.1355 at 546 nm, respectively; 3) introducing highly polarizable cations such as Hg 2+ with d 10 ‐configuration or Pb 2+ , Sn 2+ , I 5+ with lone pair electrons as in LiHgPO 4 (Δ n =0.068 at 1064 nm), Pb 2 (IO 3 )(PO 4 ) (Δ n =0.060 at 1064 nm), and Sn 2 B 5 O 9 Cl (Δ n =0.168 at 546 nm) . In particular, Sn 2 B 5 O 9 Cl exhibits a remarkable enhancement of 16 times as compared with the isostructural Ba 2 B 5 O 9 Cl.…”
Section: Figurementioning
confidence: 99%
“…Exploring new compounds with unique structures has attracted much interest of researchers, since these compounds not only enrich structural chemistry, but also may possess potential application in some areas . Borates, especially, can be regarded as an excellent candidate to explore structure unique compounds due to various coordination pattern of B (BO 3 or BO 4 ) which may be polymerized to form different fundamental building blocks (FBBs).…”
Section: Figurementioning
confidence: 99%
“…And the δ of 6MRs in the blue region, larger than 2 × δ(BO 3 ), δ(B 2 O 5 ), 3 × δ(BO 3 ) is highlighted, where the [BO 3 ] and its derived structures are birefringence-preferential structures. In particular, the [B 2 O 5 ] group can be as the benchmark owing to its dominant role in the typical birefringent material Li 2 Na 2 B 2 O 5 with a large birefringence of 0.095 measured via the prism coupling method [64]. It is indicated that the 6MRs with δ(6MRs) larger than δ(B 2 O 5 ) have the capability to produce large birefringences and possess large HOMO-LUMO gaps as screened out in Fig.…”
Section: Polarizability Characters and Microscopic Contributionmentioning
confidence: 96%